Fresno County Bar Association and Rotary Club Luncheon with State Bar President Anthony Murray - Watkins, Howard::::::::: (1983)
Anthony Murray, Rotary Club President and Judge Hollis Best, Fresno County Bar Association President-Elect Rodney Worrel at the microphone Rotary Club banners in background